Research and Implementation of Turbo Coding Technology in High-Speed Underwater Acoustic OFDM Communication. (15th March 2022) - Yang, Yarang; Li, Yunpeng
Abstract : It is demonstrated that the fully parallel turbo decoding algorithm can achieve an approximate error correction decoding performance when 36 iterations are used and when the log-map algorithm with 6 iterations is used. By comparison, it is shown that it can achieve much higher decoding rates than the log-map algorithm for various frame lengths of LTE standard turbo codes at the cost of higher hardware resource requirements. According to the fully parallel turbo decoding algorithm, this paper proposes a scheme for implementing a fully parallel turbo decoder on FPGA, detailing the overall structure and processing of the decoder hardware implementation, the design of the algorithm block processing unit, and the interleaving module. The performance of the decoder is tested by fixed-point simulation for different frame lengths of turbo coding in LTE standard, and it is proved that the fully parallel turbo decoder can be applied to turbo coding of various frame lengths. Both simulation and experimental results show that the distributed cancellation method and the joint estimation cancellation method have good results for both time-domain impulse noise and large-amplitude single frequency noise cancellation, while the joint estimation cancellation method of large-amplitude single frequency noise cancellation first has better performance.